Digital Video and Audio Broadcasting Technology - Fischer, Walter (Springer, 2017)
"Digital Video and Audio Broadcasting Technology – A Practical Engineering Guide" deals with all the most important digital television, sound radio and multimedia standards such as MPEG, DVB, DVD, DAB, ATSC, T-DMB, DMB-T, DRM and ISDB-T. The book provides an in-depth look at these subjects in terms of practical experience. In addition it contains chapters on the basics of technologies such as analog television, digital modulation, COFDM or mathematical transformations between time and frequency domains. The attention in the respective field under discussion is focussed on aspects of measuring techniques and of measuring practice, in each case consolidating the knowledge imparted with numerous practical examples. This book is directed primarily at the specialist working in the field, on transmitters and transmission equipment, network planning, studio technology, playout centers and multiplex center technology and in the development departments for entertainment electronics or TV test engineering. Since the intire field of electrical communications technology is traversed in a wide arc, those who are students in this field are not excluded either. The third edition of this well established reference work includes the new formats MPEG-4 und IPTV, and it already gives an outlook to the newest standards like DVB-SH and DVB-T2.